Giúp mình với mik cần gấp
x(x^2-1)=0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=\dfrac{y^2\left(x-2\right)\left(x+2\right)}{4xy}\cdot\dfrac{x^2y}{xy\left(2-x\right)}\)
\(=\dfrac{-y^2\left(2-x\right)\left(x+2\right)}{xy\left(2-x\right)}\cdot\dfrac{x^2y}{4xy}\)
\(=\dfrac{-y\left(x+2\right)}{x}\cdot\dfrac{x}{4}=\dfrac{-y\left(x+2\right)}{4}\)
\(\left(x+1\right)^2+\left(x^2+1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}\left(x+1\right)^2=0\\\left(x^2+1\right)=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x+1=0\\x^2+1=0\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=-1\\x^2=-1\end{cases}\Leftrightarrow}x=-1}\)
Vậy x=-1
\(\left(x-2\right)^5-\left(x-2\right)^3=0\)
\(\Rightarrow\left(x-2\right)^3\left(\left(x-2\right)^2-1\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x-2=0\\\left(x-2\right)^2-1=0\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=2\\\left(x-2\right)^2=1\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=2\\x-2=1\\x-2=-1\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=2\\x=3\\x=1\end{matrix}\right.\)
Vậy \(x\in\left\{1;2;3\right\}\)
⇒ ( x - 2)3 . (x - 2)2 - (x - 2)3 . 1 = 0 ⇒ ( x - 2)3 . [( x - 2)2 - 1] = 0
`(x-2)(2x-1)=0`
\(=>\left[{}\begin{matrix}x-2=0\\2x-1=0\end{matrix}\right.\\ =>\left[{}\begin{matrix}x=2\\x=\dfrac{1}{2}\end{matrix}\right.\)
PT có 2 nghiệm `<=> \Delta' >=0`
`<=> 4(2m+3)^2 -4(4m^2-3) >=0`
`<=>16m^2+48m+36-16m^2+12>=0`
`<=>m >= -1`
Viet: `{(x_1+x_2=-2m-3),(x_1x_2=4m^2-3):}`
Theo đề: `x_1^2+x_2^2=1/2`
`<=>(x_1+x_2)^2-2x_1x_2=1/2`
`<=>(-2m-3)^2 -2(4m^2-3)=1/2`
`<=>-4m^2+12m+15=1/2`
`<=>` \(\left[{}\begin{matrix}m=\dfrac{6+\sqrt{94}}{4}\left(TM\right)\\m=\dfrac{6-\sqrt{94}}{4}\left(L\right)\end{matrix}\right.\)
Vậy....
\(1.\)
\(x^3-x^2-x+1=0\)
\(=x^2\left(x-1\right)-\left(x-1\right)=0\)
\(=\left(x-1\right)\left(x^2-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-1=0\\x^2-1=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=1\\x=-1\end{cases}}\)
[x-2].[x mũ 2 - 16]=0
[x-2]-[x mũ 2 - 16] = 0
TH1: x-2=0
x=0+2
x=2[thỏa mãn]
TH2: x mũ 2 - 16=0
x mũ 2=0+16
x mũ 2= 16
x mũ 2=4 mũ 2 [nghĩa là 16= 4 mũ 2]
x=4
Vậy....
Bài làm
a) x( x - 1) = 0
=> x = 0 hoặc x - 1 = 0
=> x = 0 hoặc x = 1
Vậy .....
b) ( x + 1 )( x - 2 ) = 0
=> x + 1 = 0 hoặc x - 2 = 0
=> x = -1 hoặc x = 2
Vậy ...
\(x\left(x^2-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\x^2-1=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\pm1\end{cases}}\)
Vậy \(x\in\left\{-1;0;1\right\}\)
\(x\left(x^2-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x^2-1=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=0\\x=\pm1\end{cases}}\)
\(\Rightarrow x\in\left\{0;\pm1\right\}\)